Congestion and admission control in WDM optical networks - Ghaly, Mohamed A. (My University, 2006)
The demand for more communication bandwidth and network resources, has pushed researchers to find faster and more reliable data communication networks. Wavelength division multiplexing (WDM) is a promising technology to meet such increasing demands. To make use of the WDM networks, some issues need to be dealt with. This thesis discusses three problems, constraint-based path selection. Congestion Control and Admission Control. When selecting a path between the source and destination, in which some constraints are present, the choice of the path can have dramatic effects on the Quality of Service (QoS). Three path selection algorithms are compared in order to achieve optimum path selection. These algorithms are presented and analyzed in this thesis. The algorithms do not just deal with one path selection constraint but k-constraints. Two controllers are presented: A proposed congestion controller and the second is a call admission controller in circuit switched networks. The proposed congestion control algorithm is based on the fuzzy logic technique and aims to control the congestion in a WDM network through an adequate adjustment of the delay on the calls that are in the queue of the server. The adaptive admission controller for circuit switched networks is based on the optimization of resources in the network. Numerous Simulation results are presented which show the performance of each controller.
Keywords: Wavelength division multiplexing; Automatic control; Fuzzy logic